A contribution to the design of fast code converters for position encoders. Issue 10 (2nd October 2016) - Denic, Dragan B.; Dincic, Milan R.; Miljkovic, Goran S.; Peric, Zoran H.
ABSTRACT: Pseudorandom binary sequences (PRBS) are very useful in many areas of applications. Absolute position encoders based on PRBS have many advantages. However, the pseudorandom code is not directly applicable to the digital electronic systems, hence a converter from pseudorandom to natural binary code is needed. Recently, a fast pseudorandom/natural code converter based on Galois PRBS generator (much faster than previously used converter based on Fibonacci PRBS generator) was proposed. One of the main parts of the Galois code converter is an initial logic. The problem of the design of the initial logic has been solved only for some single values of resolution, but it is still not solved for any value of resolution, which significantly limits the applicability of the fast Galois code converter. This paper solves this problem presenting the solution for the design of the initial logic of the fast Galois pseudorandom/natural code converters used in the pseudorandom position encoders, in general manner, that is for any value of the resolution, allowing for a wide applicability of the fast Galois pseudorandom position encoders. Rigorous mathematical derivation of the formula for the designing of the initial logic is presented. Simulation of the proposed converter is performed in NI MultiSim software. The proposed solution, although developed for pseudorandom position encoders, can be used in many other fields where PRBS are used.